Disruptive Technologies and Nuclear Risks: What's New and What Matters. Issue 1 (2nd January 2022) - Futter, Andrew
Abstract: Hype and fear have arisen about how certain technological developments are impacting the current nuclear order. New weapons systems and support facilities, potential vulnerabilities and associated destabilising dynamics could all place considerable strain on the global nuclear balance and accompanying architecture. This article examines five disruptive dynamics, explains their intricacies and nuances, and puts them in political and strategic context. The nature of nuclear risk is changing (in many cases for the worse), and there are a number of pressures which could have significant negative implications for escalation, stability and order if left unchecked. But these phenomena remain fundamentally political, and there are political mechanisms which can help reduce risks. Accordingly, while the risks posed by disruptive technologies to the nuclear order are real and growing, they should not be insurmountable.